PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIOANAL DAN KOMPENSASI TERHADAP KINERJA PADA PT. STAR COSMOS PONTIANAK - B31111163, MISKAL (Jurnal Manajemen Update, 2017)
The purpose of this study was to determine the influence of Transformational Leadership Style and Compensation on Employee Performance at PT. Star Cosmos Pontianak either partially or simultaneously. The population in this study were all employees at PT. Star Cosmos Pontianak many as 35 people. Sample in this study amounted to 34 people not including the leadership, because leadership is a performance evaluator. The sampling method used was saturated sampling (census). Data analysis technique used is multiple linear regression analysis and hypothesis testing using t test (partial), test f (simultaneous) as well as the coefficient of determination. Â  The results of data analysis showed that the Transformational Leadership Style and Compensation partially positive and significant effect on the performance of employees at PT. Star Cosmos Pontianak significance (Î±) = 0.05. The predictive ability or the effect of variable Transformational Leadership Style and Performance Compensation amounted to 63.5%, as indicated by the value of R Square of 0.635 while the remaining 36.5% is influenced by other factors which are not included in the research model. Â  Keywords: Transformational Leadership Style, Compensation and Performance